Exploring the Health Potential of Kombucha Tea: Empowering the Community of Koto Perambahan Village: Eksplorasi Potensi Kesehatan Teh Kombucha: Pemberdayaan Masyarakat Desa Koto Perambahan - Muhammad Andry Kurniawan; Sayyidah Safiyra; Resina Mutiara; Khansa Tasya Nabila; Jasmin Khaidira Nurfatihah (Institute of Educational, Research, and Community Service, 2023)
This study explores the potential of kombucha tea in increasing the awareness and skills of the residents of Koto Perambahan Village regarding a healthy lifestyle. Through community engagement activities, this research aims to provide understanding and skills to the community regarding the production and benefits of kombucha tea. This beverage is considered to have the potential to improve digestive health, regulate blood pressure, and reduce blood glucose levels. The community engagement team delivered the material through lectures, discussions, and Q&A sessions, attended by 30 participants from the local community. This activity successfully enhanced their understanding of probiotic beverages and the skills involved in their production. Participants also experienced the variety of flavors in kombucha tea. Thus, this training is expected to increase the awareness and skills of the community in adopting a healthy lifestyle and create economic opportunities through kombucha tea production. Overall, this research has a positive impact on improving the quality of life in the village community